Public recreational activity at Taman Ria Enam Tawau / Nur Rasika Bandi - Bandi, Nur Rasika (2020)
Information related to public recreation areas in the study area, there are several methods that have been identified that can be used by residents around the area to do daily activities such as recreation, exercise, and strengthen social ties between residents in the area of Taman Ria 6's, Tawau. Methods such as parking, playground, benches, and jogging tracks are very necessary, this is because there are many residents who do various activities around the area. In addition, through the information available based on the online questionnaire, there are some problems that have been known around the public recreation area in Taman Ria 6's. Among the problems that arise are the lack of maintenance and abandoned facilities, the lack of active recreational activities and passive recreational activities. Vandalism and lack of security in this public recreation area. The use of data collection based on online questionnaires can be used by researchers to obtain data faster and interactively.